Characteristics of Bangladesh Commercial Chicken Skin and Its Crispy Product Cooked with Different Methods - Mithun, Mahmudul Hasan; Hossain, Md. Murad; Islam, Nazmul; Hosen, Tanjir; Zzaman, Wahidu; Susilo, Agus; Huda, Nurul; Talukder, Md. Khyrul Alam; Depison, Depison (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— This study investigated chicken skin as a cost-effective protein source for crispy snacks, focusing on its physical characteristics and optimal cooking methods. Chicken skin samples were collected from four suppliers—BRAC, CP, Eon, and AG group—and assessed for physical quality, including color, texture, moisture content, and presence of feathers. Visual defects such as black, red, and yellow spots were counted per kilogram to evaluate quality and freshness, with the highest quality samples selected for further testing. The AG’s chicken skin was selected for making the Crispy fried chicken skin product. The AG’s chicken skins were cut into uniform square-shaped pieces and further cooked under three different cooking conditions: immediate frying, after marinating, and after storage at room temperature (20–25°C), cooling (0–4°C), and freezing (-20°C). The results showed that AG chicken skin was the best choice for producing Crispy fried chicken skin. The storage conditions prior to the cooking process significantly affected the quality of the resulting crispy skin product. Freezing has been shown to be the most effective storage method, maintaining the appearance, taste, and texture of the skin for a long period of time, whereas storage at room temperature and chilling can cause rapid deterioration, reduce crispiness, and develop undesirable sensory characteristics. Further research is needed to ensure consistent quality in large-scale production and further refinement of the frying technique for frozen chicken skin is recommended.